Unwanted Fertility Differentials of Nepalese Mothers - Aryal, Tika Ram (Journal of Institute of Science and Technology, 2015)
This paper attempts to study unwanted fertility differentials of Nepalese mothers. Parity progression based techniques are used to estimate unwanted fertility of the Nepal Demographic and Health Survey data 2011. An estimate of unwanted total fertility rate was found to be 1.3 births per woman while wanted total fertility rate was 1.8 births per woman, and total fertility rate was 2.67 births per woman during 2009-11. About 31% of the births were accounted to be stated as unwanted births where 36% unwanted births in rural women and 25% urban women. The unwanted percentages were 28%, 38% and 41% respectively for Tarai, Hills and Mountains women. About 12% births were unwanted for educated mothers whereas 32% births were unwanted for illiterate mothers. Unwanted fertility is higher for poorest, illiterate, rural and Mountains women, which might be due to unmet need of contraception, its low use effectiveness, and getting early married as well as the lack of awareness among mothers. The findings may help research scholars, planners, policy-makers and social scientists for designing policy of a country. Journal of Institute of Science and Technology, 2014, 19(1): 45-51